Age correlated histomorphological changes in the endometrium of buffalo (Buhalus bubalis) - UPPAL, VARINDER; ROY, K S (The Indian Journal of Animal Sciences, 2014)
The present study was conducted on uterus of 24 Indian Murrah buffaloes divided into 4 groups, viz. neonatal (up to 1 month), prepubertal (below 2 years), cyclic (in diestrous phase) and pregnant (early pregnancy). The mucous of uterus was lined by stratified cuboidal or columnar in neonates which became pseudostratified columnar nonciliated from prepubeltal onwards. At places cilia were also observed in uterine epithelium of cyclic animals. During pregnancy epithelium slough otnn patches. The lamina propria of day-old calf was made up of mesenchymal cells, that were differentiating into fIbroblasts, whereas in prepubertal and pubertal animals it comprised areolar connective tissue. In early pregnancy there was marked increase in the vascularity of lamina propria. Lymphocytes. mast cells, plasma cells, polymorphonuclear leucocytes and macrophages were also seen in the lamina propria. Endometrial glands were few in number. smaller in size and were found in initial stage of formation in neonates. However, their number and size increased in later stage of development. Glands in the longitudinal section appeared as coiled tubules. They were lined by simple columnar epithelium which became cuboidal during pregnancy.